PERTANGGUNGJAWABAN MEDIS ATAS KORBAN TINDAK PIDANA MALPRAKTEK KEDOKTERAN - Ferdin Okta Wardana (Universitas Negeri Semarang, 2022)
The responsibility of the medical world to victims of criminal acts of medical malpractice is that the responsibility for the practice is an error of omission or negligence when determining the execution that results in injury or death, besides that there are no mistakes made by wrongful considerations for which the responsibility is asked. From that explanation, the formulation of the problem: the factors that cause doctors to malpractice, the regulation of medical malpractice according to Indonesian criminal law, what kind of responsibility is carried out by a medical person for malpractice according to health law, the method used is normative juridical, namely by reviewing books and also health law literature, sources of data obtained are primary and secondary legal materials consisting of the Criminal Code, Health Act and secondary legal materials consisting of books, literature and journals. The datacollection technique is carried out by how to review and review legal books related to health law. The results of this study are expected that a doctor is always careful in carrying out a medical practice so that malpractice does not occur in addition to the need for a patient to understand and also consult his illness so that a doctor understand understand the illness he suffers, for the law to be reaffirmed because it is still lacking with what is happening in the field.